2011
DOI: 10.1097/md.0b013e31822403e9
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Staphylococcus aureus Bacteremia and Sepsis in Patients With Staphylococcus aureus Colonization of Intravascular Catheters

Abstract: Two previous studies in tertiary care hospitals identified Staphylococcus aureus colonization of intravascular (IV) catheters as a strong predictor of subsequent S. aureus bacteremia (SAB), even in the absence of clinical signs of systemic infection. Bacteremia was effectively prevented by timely antibiotic therapy. We conducted this study to corroborate the validity of these findings in non-university hospitals.Using the laboratory information management systems of the clinical microbiology departments in 6 D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 7 publications
0
15
0
1
Order By: Relevance
“…A retrospective multi-center study by Hetem et al [10] showed a high rate of contamination of central venous catheters at different connection sites with Staphylococcus aureus; up to 12% of patients suffered from bacteremia after CVC removal. The contamination rate indicated in the trial of Casey et al [11] with a contamination rate of 10% for the internal surfaces of TWC luers with standard caps correspond with the data obtained in our observation.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective multi-center study by Hetem et al [10] showed a high rate of contamination of central venous catheters at different connection sites with Staphylococcus aureus; up to 12% of patients suffered from bacteremia after CVC removal. The contamination rate indicated in the trial of Casey et al [11] with a contamination rate of 10% for the internal surfaces of TWC luers with standard caps correspond with the data obtained in our observation.…”
Section: Discussionmentioning
confidence: 99%
“…A more rigorous approach to identify and limit iatrogenic sources of bacteraemia, including peripheral or central catheters,41 48 68 is required. Screening for MSSA with isolation and decolonisation has been suggested for selected high-risk patients 69…”
Section: Discussionmentioning
confidence: 99%
“…Szisztémás fertőzés esetén a klinikai tünetek és a diagnózist megerősítendő kísérő jelenségek hiányozhatnak. Lokalizált infekció esetén a bacteriaemia az időben megkezdett hatásos antibiotikum-terápiával megelőzhető [49]. Az infekció szövőd-ménye lehet a szeptikus thrombosis, endocarditis.…”
Section: Saját Vizsgálatainkunclassified